Management of Acute Anastomotic Leaks - Hedrick, Traci L.; Kane, William (Clinics in Colon and Rectal Surgery, 2021)
Management of the acute anastomotic leak is complex and patient-specific. Clinically stable patients often benefit from a nonoperative approach utilizing antibiotics with or without percutaneous drainage. Clinically unstable patients or nonresponders to conservative management require operative intervention. Surgical management is dictated by the degree of contamination and inflammation but includes drainage with proximal diversion, anastomotic resection with end-stoma creation, or reanastomosis with proximal diversion. Newer therapies, including colorectal stenting, vacuum-assisted rectal drainage, and endoscopic clipping, have also been described.
Keywords: anastomotic leak; colorectal surgery; colostomy; ileostomy; endoscopy